2015
DOI: 10.1182/blood.v126.23.2319.2319
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Rivaroxaban in Treatment of Venous Thromboembolism in Cancer Patients

Abstract: Introduction Patients with active cancer have a high risk for venous thromboembolism (VTE). The current treatment of choice for cancer-associated thrombosis is low molecular weight heparin (LMWH). Evidence for the efficacy and safety of the target-specific oral anticoagulants in the prevention and treatment of cancer-associated thrombosis is limited. In the EINSTEIN trials, comparing rivaroxaban to LMWH plus a vitamin K antagonist, only a small number of patients with active cancer received trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although direct oral anticoagulants (DOACs) are recommended for the treatment of VTE, the higher risk of recurrent VTE and major bleeding associated with cancer makes anticoagulant treatment challenging in these patients 3 . A number of clinical trials and real-world evidence studies have evaluated the use of DOACs vs. low-molecular-weight heparin (LMWH) for the treatment of cancerassociated VTE [4][5][6][7][8][9][10][11] . Based on clinical trial evidence, clinical practice guidelines have recommended DOACs be included among the treatment options for cancer-associated VTE 9,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Although direct oral anticoagulants (DOACs) are recommended for the treatment of VTE, the higher risk of recurrent VTE and major bleeding associated with cancer makes anticoagulant treatment challenging in these patients 3 . A number of clinical trials and real-world evidence studies have evaluated the use of DOACs vs. low-molecular-weight heparin (LMWH) for the treatment of cancerassociated VTE [4][5][6][7][8][9][10][11] . Based on clinical trial evidence, clinical practice guidelines have recommended DOACs be included among the treatment options for cancer-associated VTE 9,11 .…”
Section: Introductionmentioning
confidence: 99%
“… 17 Clinical trials and real-world studies have assessed DOACs including rivaroxaban and edoxaban versus LMWH for the treatment of cancer-associated VTE. 18 19 20 However, there is limited evidence for apixaban in VTE cancer patients. CARAVAGGIO, a recently completed multinational prospective, randomized, open-label, blinded end point (PROBE), noninferiority study found that apixaban was noninferior to dalteparin for the treatment of cancer-associated VTE without an increased risk of MB.…”
Section: Introductionmentioning
confidence: 99%
“…More recently however, real-world evidence from the US has shown the positive impact of rivaroxaban on resource utilisation compared with LMWH (51) and better persistence rates and fewer medication switches with rivaroxaban compared with LMWH (52). Further, data from 92 patients with active cancer in a US clinic suggests rivaroxaban can be an acceptable alternative to LMWH when used to treat CAT (53). Moreover, rivaroxaban, when used to treat 237 Canadian patients with active cancer (average duration of therapy: 297 days), was associated with low rates of recurrence and major bleeding events -of note, 47 % of those treated had metastatic disease (54).…”
Section: Discussionmentioning
confidence: 99%